2015
DOI: 10.1017/s0950268814003744
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastrointestinal illness in two Inuit communities: burden of illness in Rigolet and Iqaluit, Canada

Abstract: Food- and waterborne disease is thought to be high in some Canadian Indigenous communities; however, the burden of acute gastrointestinal illness (AGI) is not well understood due to limited availability and quality of surveillance data. This study estimated the burden of community-level self-reported AGI in the Inuit communities of Rigolet, Nunatsiavut, and Iqaluit, Nunavut, Canada. Cross-sectional retrospective surveys captured information on AGI and potential environmental risk factors. Multivariable logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 58 publications
0
53
1
3
Order By: Relevance
“…Other traditional foods linked to illness included fermented salmon eggs (stink eggs) (7,16,(21)(22)(23) and fish (such as char, salmon and trout (5,7,21). Aside from raw meat consumption, the fermentation of traditional foods was the most common traditional preparation method involved in foodborne illness (7,16,(20)(21)(22)(23)25,26).…”
Section: Type Of Traditional Foods and Traditional Preparation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other traditional foods linked to illness included fermented salmon eggs (stink eggs) (7,16,(21)(22)(23) and fish (such as char, salmon and trout (5,7,21). Aside from raw meat consumption, the fermentation of traditional foods was the most common traditional preparation method involved in foodborne illness (7,16,(20)(21)(22)(23)25,26).…”
Section: Type Of Traditional Foods and Traditional Preparation Methodsmentioning
confidence: 99%
“…Of the six documents that reported some form of trend by male/female gender, half noted approximately equal distribution for botulism (16), E. coli (28) and hepatitis A (30,31). Overcrowding in homes was noted in four articles, particularly during winter (5,29,30,31). Two studies (8,29) reported that tight social networks in small remote communities may be another possible mode of transmission for foodborne illness.…”
Section: Demographic and Social Factorsmentioning
confidence: 98%
See 3 more Smart Citations